Pandangan Masyarakat Awam Terhadap Teori Akad Dalam Transaksi Jual Beli - Anisa Latifah; Hasna Maisya Nazhirah; Muhammad Adi Wicaksono; Restu Setia Ningati; Talita Ardra Widyadhana; Edi Suresman (Yayasan Cendekia Gagayunan Indonesia, 2025)
In Islamic law, buying and selling transactions must adhere to contract principles that comply with sharia, such as mutual consent, clarity of objects and prices, and freedom from elements of gharar (uncertainty), riba (usury), and maysir (gambling). However, the general public's understanding of the concept of akad (contract) remains limited, as many perceive buying and selling merely as an exchange of goods and money without considering the legal and ethical aspects embedded in the contract. This study aims to identify the level of public understanding regarding the theory of akad in sharia-based buying and selling transactions using a qualitative approach with descriptive methods, case studies, and literature reviews. The findings indicate that although the term akad is widely recognized, in-depth understanding of its types, conditions, and principles remains inadequate. The majority of people are unfamiliar with Islamic contracts such as Murabahah, Salam, or Istishna, and they often have misconceptions regarding the elements of gharar and riba in transactions. Therefore, further education is necessary to enhance Islamic financial literacy, ensuring that buying and selling transactions align with Islamic principles, promote fairness, and avoid practices that may disadvantage one party.